Pengaruh Konten Tiktok Akun Aswaja Hijrah Terhadap Spiritualitas Remaja - Chasannudin, Arif; Nugraha, Dwi Rame (Prodi KPI FDPM IPMAFA Bekerjasama dengan Mafa Press IPMAFA Pati, 2023)
Social media is one of the online media that can be used to interact. One of the social media that exists and is fast growing is TikTok social media. The number of TikTok accounts that are used to sway and indulge, it turns out that there is a TikTok account that contains Islamic da'wah and enters FYP (for your page), namely the Aswaja Hijrah Tiktok account with 493,000 followers which is more than other da'wah accounts. This study uses quantitative methods and aims to find out whether there is a significant influence of Aswaja Hijrah account TikTok content on the spiritual development of adolescents. The results showed that based on the results of the T test, it was known that the significant value of the influence of TikTok content of the aswaja hijrah account (X) on adolescent spirituality (Y) was 0.000 < 0.05 and t count 13.945 > t table 1.966 then H0 was rejected and H1 was accepted. It can be concluded that there is a significant influence of Aswaja Hijrah's TikTok content on teenagers' spirituality. The amount of TikTok content contributed by Aswaja Hijrah Account in influencing adolescent spirituality was 32.8% while the remaining 57.3% was influenced by other variables.